2013
DOI: 10.9790/2402-0264346
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition and mineral content of the Fresh water snail (Pila ampullacea) from River Benue, Nigeria.

Abstract: The nutritional composition and mineral contents of the fresh water snail (Pila ampullacea) from Lower River Benue was investigated. This was carried out using the methods outline in Association for Official Analytical Chemist (A.O.A.C. 1995) in the Vertinary Research Institute Vom, Plateau State, Nigeria. The results obtained showed that the snail contained 76.32%±0.84 moisture, 10.67%± 0.15 protein, 0.06%± 0.02 lipids, 5.54% ±0.11 ash, 0.03%± 0.01 crude fiber and 7.40%± 0.06 Nitrogen free extract. The follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
(10 reference statements)
0
3
0
2
Order By: Relevance
“…The crude protein values obtained in this study were much lower than the values reported for edible molluscs like Crassostrea gasar (73.67%), fresh water snail (76.32%), Tympanptonus. fuscatus (70.1%) and Sepia officinalis (78.55%) by Woke et al (2016), Obande et al (2013), Davies and Jamabo (2016) and Lawal-Are et al (2018b) respectively. The highest crude protein content in this study was obtained in the peak of dry month (April).…”
Section: Discussionmentioning
confidence: 88%
“…The crude protein values obtained in this study were much lower than the values reported for edible molluscs like Crassostrea gasar (73.67%), fresh water snail (76.32%), Tympanptonus. fuscatus (70.1%) and Sepia officinalis (78.55%) by Woke et al (2016), Obande et al (2013), Davies and Jamabo (2016) and Lawal-Are et al (2018b) respectively. The highest crude protein content in this study was obtained in the peak of dry month (April).…”
Section: Discussionmentioning
confidence: 88%
“…(Tabel 1) mencapai 74,65%, lebih tinggi dibandingkan kandungan protein tepung keong mas yang diteliti oleh Zahiruddin et al, (2010) yakni 67,31%. Dalam kondisi segar rerata kandungan protein daging keong mas berkisar antara 10,67%-15,62% (Pratama & Andriani 2023;Obande et al, 2013). Tingginya kadar protein pada tepung keong mas (Tabel 1) diduga akibat perlakuan pencucian dan pengeringan yang menyebabkan protein terkonsentrasi dalam sediaan tepung.…”
Section: Kadar Proteinunclassified
“…Hasil analisis karbohidrat tepung keong mas (Tabel 1) yakni 0,17%. Dalam kondisi segar, karbohidrat dalam daging keong mas mencapai 0,03%-2,88% (Pratama & Andriani 2023;Obande et al, 2013). Syarat mutu karbohidrat dalam tepung ikan maksimum berkisar antara 1,5%-3% SNI 01-2715-1992).…”
Section: Kadar Karbohidratunclassified
“…The high protein content can be considered as a raw material for making peptone, which is the main nitrogen source in bacterial growth media. According to Obande et al (2013) the composition of the content of the conch tissue (Pila ampullacea) is 10,675 protein. The composition of the snail (Achatina fulica) network is 83.13 protein (Ossiong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%